Komunikasi Islam dalam Harmoni Keberagaman di Jawa Timur - Agoes Moh. Moefad; Maulidatus Syahrotin Naqqiyah; Barokatun Nuris Syah Riyah (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2023)
This research reveals about Islamic communication in building harmony in the diversity of society. The harmony of diversity in this case is intended to neutralize phenomena in society that are "triggered" by problems of differences in understanding or belief in religion in the province of East Java. This research focuses on how the form of Islamic communication carried out by mosques in building harmony in the diversity of beliefs among fellow Muslims (different understandings) and how the process of building harmony in the diversity of people's beliefs (different religions) in the East Java region. This research uses a qualitative descriptive method with a constructivist approach. Research shows that in forming harmony for diversity in the province of East Java, mosques need a control system in managing mosque management. The management includes the secretariat, leadership aspects, and the ownership status of the mosque because this is none other than one of the triggers for the emergence of "conflict" within Islam itself. Apart from that, the mosque also held entrepreneur-based Rema's cadre training, as well as monitoring preachers and mosque labeling. This is intended to reduce the occurrence of conflicts due to negative stigma in society.